Understanding hemoglobin contribution to high-dose methotrexate disposition—population pharmacokinetics in pediatric patients with hematological malignancies - Škorić, Biljana; Jovanović, Marija; Kuzmanović, Miloš; Miljković, Branislava; Vučićević, Katarina (European journal of clinical pharmacology, 2024)
Purpose The aim of the present study was to develop a population pharmacokinetic model for methotrexate (MTX) during high-dose treatment (HDMTX) in pediatric patients with acute lymphoblastic leukemia (ALL) and non-Hodgkin’s lymphoma (NHL) and to describe the influence of variability factors. Methods The study included 50 patients of both sexes (aged 1–18 years) who received 3 or 5 g/m 2 of HDMTX. A nonlinear mixed effect modeling approach was applied for data analysis. Parameter estimation was performed by first-order conditional estimation method with interaction (FOCEI), whereas stepwise covariate modeling was used to assess variability factors. Results The final model is a two-compartment model that incorporates the effect of body surface area and the influence of hemoglobin and serum creatinine on MTX clearance (CL). Population pharmacokinetic values for a typical subject were estimated at 5.75 L/h/m 2 for clearance (CL), 21.3 L/m 2 for volume of the central compartment (V1), 8.2 L/m 2 for volume of the peripheral compartment (V2), and 0.087 L/h/m 2 for intercompartmental clearance (Q). According to the final model, MTX CL decreases with increasing serum creatinine, whereas a positive effect was captured for hemoglobin. A difference of almost 32% in MTX CL was observed among patients’ hemoglobin values reported in the study. Conclusion The developed population pharmacokinetic model can contribute to the therapy optimization during HDMTX in pediatric patients with ALL and NHL. In addition to renal function and body weight, it describes the influence of hemoglobin on CL, allowing better understanding of its contribution to the disposition of HDMTX.